Wind dancer - Platt, Chris, 1959- (Peachtree Publishers, 2014)
Having lost her beloved pony in a traumatic accident, thirteen-year-old Ali is reluctant to help her parents care for a neglected, malnourished Appaloosa but working with Wind Dancer is a good distraction from problems surrounding her brother, who recently returned from Afghanistan with a missing leg and PTSD.